Effect of microstructure softening events on the chip morphology of AISI 1045 steel during high speed machining. Issue 9 (February 2016) - Pu, C.; Zhu, G.; Yang, S.; Yue, E.; Subramanian, S.
Abstract The main purpose of this paper is to study the change of chip morphology with increasing cutting speed by considering the role of microstructure evolution in chip root. The orthogonal cutting experiments of AISI 1045 steel showed that the chip morphology would be changed from continuous chip to discontinuous serrated chip as the microstructure softening events occurred in the secondary shear zone with the increasing cutting speed. Based on the principle of cutting force balance and the concept of equilibrium shear angle (ϕ e ), the influence of the dynamic behavior of deformation and recrystallization in chip material on chip morphology was analyzed and modeled. Three types of chip morphology would be characterized corresponding to the sliding, only severe deformation and dynamic recrystallization behaviors, respectively, in the secondary shear zone. It was concluded that the physical mechanism of the serrated chip morphology is the variation ofϕ e controlled by the mechanical properties of workpiece material in the secondary shear zone, which is related to dynamic deformation behavior of material as influenced by microstructural softening events, such as recrystallization or phase transformation.